Coculture with hematopoietic stem cells protects cardiomyocytes against apoptosis via paracrine activation of AKT - Rosenberg, Mark; Lutz, Matthias; Kühl, Constantin; Will, Rainer D.; Eckstein, Volker; Krebs-Haupenthal, Jutta; Katus, Hugo; Frey, Norbert (Journal of translational medicine, 2012)
Previous experimental studies concluded that stem cells (SC) may exert their beneficial effects on the ischemic heart by paracrine activation of antiapoptotic pathways. In order to identify potential cardioprotective mediators, we performed a systematic analysis of the differential gene expression of hematopoietic SC after coculture with cardiomyocytes (CM).